2022
DOI: 10.1186/s12891-022-05970-x
|View full text |Cite
|
Sign up to set email alerts
|

Complications of injections in conservative treatment of degenerative spine disease: a prospective unicentric study

Abstract: Background Spinal injection has been an accepted part of conservative therapy for degenerative diseases. The drugs used can cause side effects and severe complications. The aim of this study was to determine the occurrence of general side effects (GSE) and complications when performing consecutive different types of spinal injections and to evaluate pain reduction. Methods Prospective data evaluation of patients with degenerative spine disease at h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
(39 reference statements)
0
3
0
1
Order By: Relevance
“…The failure rate was 26% in steroid injections and 14% in PRP injections. Two articles about SIJ steroid injections reported a high rate (19 and 50%) [ 21 , 22 ] of unspecified complications, while the other studies reported a lower number of complications: overall, the complication rate was 1% in steroid injections and 1% in PRP injections. The used scores were heterogeneous (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The failure rate was 26% in steroid injections and 14% in PRP injections. Two articles about SIJ steroid injections reported a high rate (19 and 50%) [ 21 , 22 ] of unspecified complications, while the other studies reported a lower number of complications: overall, the complication rate was 1% in steroid injections and 1% in PRP injections. The used scores were heterogeneous (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The administration of contrast media during ESI can lead to serious adverse effects, including anaphylactic shock in patients with allergies to contrast agents and contrast-induced acute kidney injury in patients with pre-existing renal conditions [ 28 ]. Furthermore, our study suggests that performing ESI without contrast media leads to decreased radiation exposure and shorter operation time for patients.…”
Section: Discussionmentioning
confidence: 99%
“…Voelker 등( 54 )은 주사 방법에 따라 부작용 발생률이 다르다고 보고했다. 일시적인 두통은 경막 외 추궁판간 주사 그룹에서 가장 흔하게 나타났으며(13.5%), 후관절 주사 그룹에서 가장 드물게 나타났다(1.8%).…”
Section: 안전성(Safety)unclassified